Uncommon involvement of multiple lesions in the oral cavity: A case report (Research, Society and Development, 2021)
In maxillomandibular complex lesions of various etiolopathogenesis may occur. Commonly, lesions are solitary, however, in in rare cases, multiple lesions with distinct natures affect the maxillo-mandibular complex. Until now, the recent literature, there are no reports of simultaneous impairment of periapical cysts, dentigerous and cementoblastoma in the same patient. We report the case of a 38-year-old with syndromic appearance, short stature, brachyfacial, showing hypertelorism, but no definitive diagnosis with multiple oral lesions in the jaws. In the reported case, a residual periapical cyst associated with the swelling in the anterior region of the maxilla occurring simultaneously to a dentigerous cyst and associated with tooth 35 cementoblastoma included. Despite the simultaneous involvement of multiple lesions with different etiopathogenesis is uncommon in the literature, this report seeks to emphasize the importance of thorough and systematic clinical examination, promoting proper conduct of maxillary lesions and perform the correct treatment.